ANALISIS TOTAL ASSETS TURN OVER DAN CURRENT RATIO TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN Tbk SEKTOR PERTANIAN YANG TERDAFTAR DI BURSA EFEK INDONESIA DENGAN RETURN ON EQUITY SEBAGAI VARIABEL INTERVENING - Ulfa, Maria; Karnadi, Karnadi; Sari, Lita Permata (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The activity ratio is an illustration of the extent to which a company manages its assets in order to maximize the company's activities. In this study, the activity ratio as a proxy for Total assets turnover is used to calculate the rotation of all company-owned assets and to calculate all sales generated from these assets so that it will be known how effectively the company uses its asset sources. If the value of total asset turnover is high, the company's assets will be better in earning profits, this is an opportunity for investors to invest and trigger an increase in the market price of a company's shares. The purpose of this study is to determine the analysis of total assets turnover and current ratio to firm value in agricultural sector listed companies on the Indonesia Stock Exchange with return on equity as an intervening variable. Random sampling method (simple probability sampling) without regard to strata in the population in this study. Data analysis and hypothesis testing in this study used the Structural-partial Least square equation model (PLS-SEM). The results of the hypothesis test have a direct effect using the smart PLS 3.0 application, indicating that Total Asset Turn Over has a significant negative effect on the Ratio on Equity. Current Assets have a significant positive effect on the Ratio on Equity. Total Asset Turn Over has a significant positive effect on Firm Value. Current Assets have a significant negative effect on Firm Value. The ratio on Equity has a significant positive effect on Firm Value. Total Asset Turn Over has no significant negative effect on Firm Value through the Ratio on Equity. Current Assets have no significant positive effect on Firm Value through the Ratio on Equity.